Hubungan antara Kecerdasan Emosional dengan Kontrol Diri dan Kecemasan Pada Atlet Tim Bago Futsal Club (BFC) di Tulungagung - Prasetyo, Achmad; Nurkholis, Moh.; Herpandika, Reo Prasetiyo (Journal of Physical Activity and Sports (JPAS), 2024)
This research was motivated by the results of the researcher's observations, when the researcher interviewed the coach of the Bago Futsal Club team, namely Bagus Atmojo at Global Futsal Tulungagung, he said that on the field, athletes when competing often cannot control their emotions well, thus disrupting individual and team play. One example is that athletes lack focus and are always carried away by emotions. The emotions that occur here do not have a positive impact on the athlete or team but rather have a negative impact. Then, when the researcher trained the team directly and went out into the field, the researcher saw for himself that sometimes the players felt anxious when they saw opponents who were superior or above the players, not to mention the ridicule or ridicule from the opposing supporters, which caused the players' mental and performance to decline before doing a match. And often there is a lack of self-control from players when they are on the field. This research uses a quantitative approach with a survey method. The research subjects were all athletes from the Bago futsal club team, totalling 53 athletes. Data was collected through a questionnaire that was distributed to all athletes. Based on the results of the analysis, it shows that: The mean value of variables themselves (mean value 2.32)(low), 4. Recognizing other people's emotions (mean value 2.22)(low), 5. Building relationships (mean value 2.56)(high). Meanwhile, the mean value of variable Y1 has 2 indicators, namely 1. Intrinsic (mean value 2.84)(high), 2. Extrinsic (mean value 2.52) and Y2 there are 2 indicators, namely 1. Intrinsic (mean value 2.84) (high), 2. Extrinsic (mean value 2.52). Then there was a significant relationship between emotional intelligence self-control and anxiety in athletes from the Bago Futsal Club (BFC) team in Tulungagung with a correlation value of 0.744.